MEKANISME SEKSUALISASI LAKI-LAKI DALAM WEBTOON EGGNOID - Bizanti Ayuri Ganis Daulay; Hapsari Dwiningtyas Sulistyani (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2019)
Comics that were originally published conventionally, are now publishedvia the internet, known as Webtoon. Webtoon developed in line with the rapiddevelopment of internet content. In the media, it is seen that sexualization is notonly applied to female, but has also been applied to male, especially the mediathat based on female demographics.The Eggnoid, a female demographic based webtoon, shows its own mechanism ofmale sexualisation.The objective of this study is to identify and analyze how the mechanismof male sexualisation in Eggnoid carried out through visual-image construction ofmale protagonist characters and power dynamic between male and femaleprotagonist characters. This study uses a qualitative approach by using thesemiotic-analysis of Charles S. Peirce, emphasizes the semiotic analysis of signs,which divided into three areas; the icon, the index and the symbol. This study isalso supported by the APA's sexualisation theory, the Scott McCloud's comictheory, and the theory of power by Fred Luthans.The results show that Webtoon Eggnoid presents the mechanism of malesexualisation, from its beautifully face drawing, larger eyes and soft, the athleticbody shape of male protagonist, the bright skin coloring techniques with halo orflower backgrounds that give a dreamy effect. In other words, Eggnoid shows themale protagonist picture has been designed intentionally based on female beautystandards. Eggnoid shows the power dynamics between male and femaleprotagonists, starting from season one, two and three. The female protagonistshows a dominant role than the male protagonist initially, but in season three, themale protagonist is started to play a dominant role, by presenting his maturity ofthinking and taking initiatives when interacting with female protagonist. Althoughmale protagonist appears to be more dominant, Eggnoid points out that femaleprotagonist is still hold real power. It is reflected by the intention of maleprotagonists who behave to meet only the interests of female protagonist.